Antibacterial Activity of Suruhan Leaf Extract (Peperomia pellucida L) Against Staphylococcus aureus - Nadyah Maharani; Galuh Anggraini; Valentino Haksadjiwo; Bambang Nuryadi; Rosada Sintya Dwi (Sriwijaya Journal of Dentistry, 2023)
Introduction: Staphylococcus aureus is one of the opportunistic bacteria in the oral cavity that can cause various diseases, including periapical abscesses. Microbial infection treatment must pay attention to selected antibiotics. Traditional medicine was very popular with the community because it had very minimal side effects and the availability that is easy to obtain. Suruhan leaves could be utilized as an antibacterial due to their content of tannins, saponins, flavonoids, and alkaloids, which inhibit bacterial growth. Purpose: This study aimed to determine the effectiveness of the antibacterial extract of suruhan leaves (Peperomia pellucida L) against Staphylococcus aureus. Methods: This study was an in vitro laboratory experimental study. The test group used an extract of suruhan leaf with concentrations of 20%, 40%, and 60% obtained by the soxhlation method. Clindamycin was used as a positive control, and distilled water as a negative control.  The antibacterial potency was tested using the disc diffusion method to determine the value of the inhibition zone, and the dilution method to determine the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC). The inhibition zone values were then analyzed statistically using one-way ANOVA and post-hoc Tukey tests. Results: This study revealed that the 60% concentration of extract suruhan leaf had an average inhibition zone of 18.27 mm, but smaller than clindamycin. The MIC test results of extract suruhan leaf were determined at a concentration of 20% and MBC at 40%. Conclusion: Suruhan leaf extract (Peperomia pellucida L.) had antibacterial activity against Staphylococcus aureus.